Analisis Perbandingan Menggunakan Metode Waspas (Weight Aggregated Sum Product Assesment) dan AHP(Analitycal Hierarchy Process) Pemilihan Aplikasi Smartphone Untuk Anak Tingkat SD - Emma Yurispa Siregar; Sumi Khairani; Rismayanti (Jurnal Ilmu Komputer dan Sistem Informasi, 2022)
The use of applications in elementary school level children has had a bad impact because they are addicted to playing online games, social media and spending their time just playing applications on the smartphone. The problem in this study is the bad effect of an application on a smartphone for elementary school children. During the current pandemic, smartphones are tools used by children in the learning process, most children today have many minors who abuse an application on the smartphone, which causes them to no longer focus on learning but are addicted to using smartphones, namely because of the application. what they like, as a result they are lazy to learn. Therefore the authors designed a decision support system on comparative analysis using two methods, namely the WASPAS and AHP methods with specified criteria. The two methods are compared to find out which method is more effective, easy and fast in the calculation process that can help in determining which applications on smartphones are good to use for children at the elementary level.